Trajectory Tracking pada Robot Omni dengan Metode Odometry - Fahmizal Fahmizal; Dhiya Uddin Rijalussalam; Ma’un Budiyanto; Afrizal Mayub (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
This paper presents trajectory tracking on omni robots using odometry method. The odometry system aims to estimate the position relative to the initial position of the omni robot to estimate changes in position over time. The rotary encoder sensor is used to count the movement of the omni robot at the xand y coordinates in the odometry calculation process in this study. Furthermore, using the reverse kinematics on the omni robot, the rotational speed value of each DC motor in the omni robot wheel is obtained. In addition, to obtain the results of a good robot movement on the odometry system, PID control is applied to control the rotational speed of each DC motor on the omni robot wheel. With reverse kinematics and odometry systems, omni robot trajectory designs can be easily built. To test the odometry method performance in trajectory tracking process, there are three types of trajectory testing patterns, namely rectangles, equilateral triangles, and equilateral triangles. From the results of this test, the error value obtained is below 5%.